CAVE INVERTEBRATES IN NORTHWESTERN MINAS GERAIS STATE, BRAZIL: ENDEMISM, THREATS AND CONSERVATION PRIORITIES - Matheus Henrique Simões; Marconi Souza-Silva; Rodrigo Lopes Ferreira (Acta Carsologica, 2014)
Due to their high economic value, karstic areas and caves have been affected for decades in Brazil. Accordingly, such systems have been receiving the attention of managers, environmental agencies and researchers, especially in recent years. The present study collected information regarding the cave invertebrate fauna of the Northwest region of Minas Gerais, Brazil, such as species richness and endemisms, besides the impacts and threats occurring in these environments, identifying caves and more vulnerable areas and  proposing conservation actions. Three caves were identified as a priority for conservation: Lagoa Rica cave in Paracatu, and Lapa Nova and Lapa da Delza caves in Vazante. Another three areas were considered in need of conservation actions: regions of Arinos, Paracatu and Cabeceira Grande/Unaí. The main threat found in the area was the conversion of forests into pastures for cattle breeding, registered in the surroundings of 85% of the caves. The main recommendations were the recuperation of the surroundings, awareness raising of the population and biospeleological inventories in other caves of the area. The studied caves were very heterogeneous, presenting unique characteristics. Thus, the study of the highest possible number of caves of the region of interest is always recommended, to aid in conservation and action plans for cave fauna.